Developing Teaching Material Used Project-based Learning to Improve Student's Research Skills - Sutiyono, Agus; Apriliana, Evita Nur; Putri, Alfi Rahmania; Chantarosombat, Chalard (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
This research is intended to develop teaching materials for learning theories courses and test the feasibility of the learning materials products. This research seeks to uncover problems and challenges in learning theories courses from the perspective of lecturers and students. The subjects of this study are students and lecturers of the master program in Islamic Religious Education, Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Walisongo Semarang. This research applies a 4D development model to develop teaching materials, which includes four stages: defining, design, development, and dissemination. Researchers use questionnaires and focus group discussions involving lecturers and students. The result of the development in this study is teaching materials of project-based learning teaching materials for learning theories courses. Based on expert validation tests, material experts, curriculum experts, and media design experts declare that teaching materials for project-based learning theories courses are feasible with a scoring average of 81,79%. After being applied to the learning theories course, out of 60 students, 75.17% strongly agreed, 22.17% agreed, and 2.67% disagreed that the teaching materials using Project-Based Learning improved student research skills and helped students more easily understand the course. From the lecturer's point of view, using Project Based Learning (PjBL) in learning theory courses can allow students to learn actively, collaborate with classmates, and develop better research skills. Therefore, implementing PjBL in learning theory courses can effectively improve the quality of learning and student understanding.